CDS/ISIS software for libraries - Matovelo, Doris; Smet, Egbert de (Technical Centre for Agricultural and Rural Cooperation, 2005)
Doris Matovelo and Egbert de Smet explain why Sokoine National Agricultural Library in Tanzania chose CDS/ISIS software to administer its catalogue and other library operations.